Implementation of input-process-output model for measuring information system project success - Subiyakto, A'ang; Ahlan, Abdul Rahman (UAD and IAES, 2014)
Measurement of the information system (IS) project success has become the interesting topic for researchers and practitioners since the Standish Group published their findings in 1994. Project success theory is the main concept in this topic, but this theory is still an ambiguous concept and lack in agreement among researchers and practitioners. They are also still tending to focus on single or partial dimension. Therefore, they did not get a clear picture of the system measurements. This study developed an alternative model of the project success measurement based on input-process-output (IPO) model. The development was conducted using comparison, adoption, adaptation, and combination the previous theories and models: Davis's IPO model, the project success theories, Delone and McLean' model, and the project classificatory framework. As indicated in most studies that most of models are developed using the previous theories and models rather than on empirical proofs. The result is a IS project success model consisting of 9 variables and 36 relationships among the variables. Although, the model is only a conceptual model, but it was developed completely and coherently considering three main aspects of project success measurement, namely: processional and causal models, project success theories, and the influence concept of project environment.